Pemanfaatan smartphone dalam menciptakan animasi stop motion sebagai alternatif media ajar guru SMK Multimedia - Maya Purnama Sari; Dian Rinjani; Fahmi Candra Permana; Intan Permata Sari; Nurul Hidayah (Universitas Pendidikan Indonesia (UPI), 2021)
Community Service based on research results in 2019, the results of the applied research are the basic techniques of creating an illustrated digital image into animation with the characteristics of a flat-space-time image and the basic stopmotion video editing techniques applied using a smartphone. The stopmotion technique is a basis that can be utilized optimally, the Covid-19 pandemic situation which limits the use of school computer laboratory facilities is a learning obstacle for students who do not have personal computers. The practical use of smartphones is able to produce good stopmotion video animation works, so the training focuses on SMK Multimedia teachers. The goal is that teachers can optimize smartphones to create stopmotion video animations as a way of learning for their students. The action review method is used so that the implementation of effective and solution training uses eight steps, namely problem identification, problem formulation, alternative identification, alternative determination, planning, program implementation, monitoring, evaluation and action review. The target audience is SMK Karya Budi's Multimedia Department, Cilenuyi District, Bandung Regency, totaling 11 people consisting of 5 expertise teachers and 6 adaptive normative teachers. The training is conducted offline and online. The results of the evaluation show that the teacher needs the help of video tutorials to repeat the training more, but overall the teacher is able to create animation from illustration images of the features of flat-space-time images and stop motion video editing using applications on smartphones.